Christianity and Culture in the City : a Postcolonial Approach. - Cruz, Samuel (Lexington Books, 2012)
This volume examines how the manifestation and development of diverse expressions of Christianities in the city offer potentialities and innovative models for the liberation struggles and gospel incarnation within various social, historical, economic, cultural/ethnic, sexual, and gender realities. In the thick of struggling communities in our changing city contexts, this book offers a conceptual and practical map for viewing the complex realities that shape and impact the presence and transformation of Christianities in city life.